This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 104, Solution to Homework 12 Instructor: Guoliang Wu August 6, 2009 Ross, K. A., Elementary Analysis: The theory of calculus : 26.3 (a) Since X n =1 nx n = x (1 x ) 2 for  x  &lt; 1 , d dx X n =1 nx n = d dx x (1 x ) 2 X n =1 n 2 x n 1 = 1 (1 x ) 2 + 2 x (1 x ) 3 = 1 + x (1 x ) 3 X n =1 n 2 x n = 1 (1 x ) 2 + 2 x (1 x ) 3 = x (1 + x ) (1 x ) 3 ,  x  &lt; 1 . (b) Plug in x = 1 2 and x = 1 3 , X n =1 n 2 2 n = 1 2 (1 + 1 2 ) (1 1 2 ) 3 = 6 , X n =1 n 2 3 n 1 3 (1 + 1 3 ) (1 1 3 ) 3 = 3 2 . 26.6 (a) s ( x ) = X n =0 ( 1) n x 2 n +1 (2 n + 1)! = X a m x m , where a m = , m is even ( 1) n (2 n +1)! , m = 2 n + 1 1 So = lim sup  a m  1 /m = lim n ( 1) n (2 n + 1)! 1 / (2 n +1) = lim k 1 k ! 1 /k = lim k k ! ( k + 1)! = 0 . Thus R = 1 = + . So s is differentiable on R and can be differentiated term by term: s ( x ) = X n =0 ( 1) n (2 n + 1) x 2 n (2 n + 1)! = X n =0 ( 1) n x 2 n (2 n )! = c ( x ) . Moreover, the series for c ( x ) also has radius of convergence R = and can be differentiable term by term on R , so c ( x ) = X n =1 ( 1) n (2 n ) x 2 n 1 (2 n )! = X n =1 ( 1) n x 2 n 1 (2 n 1)! = X n =0 ( 1) n x 2 n +1 (2 n + 1)! = s ( x ) . (b) ( s 2 + c 2 ) = 2 ss + 2 cc = 2 sc + 2 c ( s ) = 0 . (c) Since ( s 2 + c 2 ) = 0 , the function s 2 + c 2 is a constant. Be cause s 2 (0) + c 2 (0) = 0 + 1 = 1 , s 2 + c 2 = 1 , x R ....
View Full
Document
 Winter '08
 staff
 Calculus

Click to edit the document details